2016
DOI: 10.1111/apha.12744
|View full text |Cite
|
Sign up to set email alerts
|

Bladder pain induced by prolonged peripheral alpha 1A adrenoceptor stimulation involves the enhancement of transient receptor potential vanilloid 1 activity and an increase of urothelial adenosine triphosphate release

Abstract: This study suggests that the activation of peripheral alpha 1A adrenoceptors induces CVP, probably through its interaction with TRPV1 and ATP release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…NE containing nerves are found in the mucosa in close proximity to UTC, suggesting possible interactions between sympathetic fibers and UT. UTC express α‐AR and β‐AR . Our results show that stimulation of α‐ARs but not β‐ARs in cultured rat UTC resulted in ROS production (Figure D).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…NE containing nerves are found in the mucosa in close proximity to UTC, suggesting possible interactions between sympathetic fibers and UT. UTC express α‐AR and β‐AR . Our results show that stimulation of α‐ARs but not β‐ARs in cultured rat UTC resulted in ROS production (Figure D).…”
Section: Discussionmentioning
confidence: 67%
“…Our results show that stimulation of α‐ARs but not β‐ARs in cultured rat UTC resulted in ROS production (Figure D). Other studies have shown that exposure of cultured human UTC to the α‐AR agonist phenylephrine, results in increased ATP release in response to mechanical stimulation when compared to control cells and in the WAS rodent model an α1‐AR antagonist reversed bladder frequency, urinary NE excretion as well as changes in the morphology of the UT . Thus, urothelial α‐ARs seem to play significant roles in mediator release and oxidative stress, both of which can influence afferent nerve excitability and pain pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Birder et al (2002a) studied the TRPV1 channel in a TRPV1 knockout (À/À) mouse model and detected an increased bladder capacity and a decrease in ATP excretion during bladder distention, implying that the TRPV1 receptors may also regulate normal bladder filling mechanosignalling. Charrua et al confirmed these results by detecting an increase in urothelial ATP excretion after TRPV1 activation (Charrua et al 2009, Matos et al 2016. OAB is associated with Cfibre activation and bladder instillation with TRPV1 agonists like capsaicin or the superagonist resiniferatoxin has been clinically applied in humans to desensitize these normally silent nerves to reduce the symptoms of OAB.…”
Section: Mechanoreceptorsmentioning
confidence: 91%
“…, Matos et al . ). OAB is associated with C‐fibre activation and bladder instillation with TRPV1 agonists like capsaicin or the superagonist resiniferatoxin has been clinically applied in humans to desensitize these normally silent nerves to reduce the symptoms of OAB.…”
Section: Mechanosensationmentioning
confidence: 97%
“…Based on their results, Charrua et al [ 47 ] concluded that excessive adrenergic stimulation of the bladder may contribute to the pathophysiological mechanisms of BPS/IC. In a follow-up study, Matos et al [ 53 ] showed that phenylephrine-induced morphological bladder changes, bladder overactivity, and L6 spinal cord Fos expression, were reversed by the highly selective α 1A -AR antagonist, silodosin, but not by naftopidil, a relatively selective antagonist for α 1D -ARs. Prazosin (which blocks all subtypes of α 1 -ARs) had an intermediate effect.…”
Section: Reduction Of Sympathetic Overactivity and Stressmentioning
confidence: 99%